Formulasi Sediaan Masker Clay Kombinasi Ekstrak Daun Pepaya (Carica papaya L.) Dan Daun Sirsak (Annona muricata L.) - Alfiraza, Ery Nourika; Endang Istriningsih; Nadiyya Rizka Maulana (Universitas Airlangga, 2024)
One type of cosmetic product used to care for facial skin is a mask. Clay masks are masks that contain mineral materials derived from clay, especially kaolin and bentonite. The purpose of this study was to determine the difference in concentration in formula F0 (0:0) FI(2:6), formula FII (4:4), and formula FIII (6:2) with a combination of papaya leaf extract and soursop leaf in clay mask preparations. This study uses an experimental approach, which starts with preparing a mask preparation and then evaluating the mask preparation. The results of One Way Anova's data analysis show that the sig value is 0.000 < 0.05, which means that H0 is rejected. The results of organoleptic, pH, homogeneity, dispersion, adhesion, dry time, viscosity, irritation, and stability showed that all concentrations of formula F0, FI, FII, and FIII met the requirements. The results of all concentration differences in F0, FI, FII, and FIII showed that the combination of papaya leaf extract and soursop leaf extract could be made in clay mask preparations. Keywords: Papaya Leaves, Soursop Leaves, Mineral Clay